The impact of college students’ parent–child attachment on bullying behavior: the mediating role of external expression of anger - Wang, Ruixin; Chen, Yiwen; Zhao, Zhenyu; Zhao, Mengmeng; Wang, Ziying; Luo, Hongge; Li, Lina (Frontiers in Psychology, 2024)
Purpose (1) To investigate the relationship between college students’ parent–child attachment, external expression of anger, and bullying behavior; (2) To explore the mediating role of external expression of anger between parent–child attachment and bullying behavior. Methods The Parent–Child Attachment Scale, State–Trait Anger Expression Inventory, and Bullying Participation Behavior Questionnaire were administered to 306 college students. Data collected were analyzed using SPSS 26.0 for common method bias tests, descriptive analysis, and correlation analysis. The mediation model was tested using the PROCESS macro program. Results Parent–child attachment was significantly negatively correlated with external expression of anger and bullying behavior, while external expression of anger was positively correlated with bullying behavior. Additionally, the external expression of anger partially mediated the impact of parent–child attachment on bullying behavior. Conclusion This study clarifies the relationship between parent–child attachment, external expression of anger, and bullying, emphasizing the indirect effect of parent–child attachment on individual bullying behavior through the external expression of anger. It provides data support for the further development of innovative methods to effectively reduce bullying behavior.